2021
DOI: 10.1038/s41467-021-27383-5
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation upon low-speed solid–liquid impact

Abstract: When a solid object impacts on the surface of a liquid, extremely high pressure develops at the site of contact. Von Karman’s study of this classical physics problem showed that the pressure on the bottom surface of the impacting body approaches infinity for flat impacts. Yet, in contrast to the high pressures found from experience and in previous studies, we show that a flat-bottomed cylinder impacting a pool of liquid can decrease the local pressure sufficiently to cavitate the liquid. Cavitation occurs beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Shock waves from collapsing cavitation bubbles have been the subject of interest to academics and industrialists due to their extraordinary potential of generating severe response dynamics in a variety of fields, ranging from biomedical sciences, nanomaterials, food processing, microelectronics, to liquid metal processing and additive manufacturing [1] , [2] , [3] , [4] , [5] , [6] . Also recently, fundamental studies investigated the spatial shock wave pressure in the cavitation centre and the threshold of shock waves upon solid–liquid impact respectively [7] , [8] further advancing the existing knowledge in the field. Hence, understanding the acoustically-induced cavitation shock waves, and specifically the detection and elucidation of acoustic signals (that can be used as a powerful tool to control cavitation activity during ultrasonic processing as in [9] , [10] ) emanated from bubble activity is vital for the development and further improvement of various applications and techniques allied to these fields.…”
Section: Introductionmentioning
confidence: 99%
“…Shock waves from collapsing cavitation bubbles have been the subject of interest to academics and industrialists due to their extraordinary potential of generating severe response dynamics in a variety of fields, ranging from biomedical sciences, nanomaterials, food processing, microelectronics, to liquid metal processing and additive manufacturing [1] , [2] , [3] , [4] , [5] , [6] . Also recently, fundamental studies investigated the spatial shock wave pressure in the cavitation centre and the threshold of shock waves upon solid–liquid impact respectively [7] , [8] further advancing the existing knowledge in the field. Hence, understanding the acoustically-induced cavitation shock waves, and specifically the detection and elucidation of acoustic signals (that can be used as a powerful tool to control cavitation activity during ultrasonic processing as in [9] , [10] ) emanated from bubble activity is vital for the development and further improvement of various applications and techniques allied to these fields.…”
Section: Introductionmentioning
confidence: 99%
“…After the pressure wave hits the air film, it will be reflected to form a rarefaction wave. Due to the effect of the rarefaction wave, the local pressure drops below the vapor pressure to produce cavitation [2] , [39] . Pulsating microbubbles are generated near the gas film ( t = 1.57 ms).…”
Section: Multiple Jet Modes With Air Wall Conditionsmentioning
confidence: 99%
“…Cavitation erosion is a complex physical phenomenon involving solid–liquid-vapor multiphase, which is also a classic physical problem [1] . When the local pressure underwater is less than the vapor pressure, bubbles spill out of the water and cavitation occurs [2] , [3] , [4] , [5] . According to the generalized Bernoulli principle (where the flow velocity is high, the pressure is low), in engineering practice, this phenomenon mostly occurs in areas where water flows at a high speed, such as underwater propellers [6] , [7] , ship rudders [8] , water pumps [9] , [10] , valves [11] , [12] , right-angle pipes [13] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Speirs et al. (2021) investigated the impulsive impact of a flat bottom cylinder experimentally, accounting for the small compressibility of water. Not only did they find high pressures similar to previous studies, but they also revealed a decrease in the local pressure sufficient to cavitate the liquid.…”
Section: Introductionmentioning
confidence: 99%